Pest Management Needs and Limitations for Corn Earworm (Lepidoptera: Noctuidae), an Emergent Key Pest of Hemp in the United States. Issue 1 (11th September 2021) - Britt, Kadie E; Kuhar, Thomas P; Cranshaw, Whitney; McCullough, Christopher T; Taylor, Sally V; Arends, Benjamin R; Burrack, Hannah; Pulkoski, Melissa; Owens, David; Tolosa, Tigist A; Zebelo, Simon; Kesheimer, Katelyn A; et al.
Abstract: Corn earworm, Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae), has emerged as an injurious insect pest to hemp, Cannabis sativa L., a crop newly reintroduced to the United States. Growing hemp presents a potential alternative economic opportunity for farmers but can be challenging with a market that is unstable and just developing. One of the most notable production challenges is managing corn earworm, an insect pest that is particularly damaging when it feeds on flower buds produced in cannabinoid varieties, creating extensive bud tunneling and wounds that allow entry of pathogens that can aid development and presence of bud rot. Damage to seeds is of lesser concern in hemp cultivars grown for grain and minimal risk is associated with hemp grown for fiber. Our ability to research hemp has only recently been allowed as production was largely suspended following World War II and, as such, there has been limited opportunity to develop information for empirically-based pest management recommendations. Further complicating development of integrated pest management (IPM) strategies are regulatory challenges associated with providing registration support to add hemp to pesticide labels, as it was not formally recognized as a crop by U.S. regulatory agencies until late 2019. Research needs and challenges to develop effective IPM programs for corn earworm on hemp are discussed here.